Correlation between Commitment and Organizational Performance - Dafiq, Muhammad; Solihat, Asri (Rescollacom (Research Collaborations Community), 2023)
Organizations are basically social units that are intentionally formed and may be reformed by taking into account the effectiveness and efficiency of achieving a particular goal. In addition, the role of the workforce of a company is essential because it is the main driver in running a smooth business and the company's performance; hence, it is considered as one of the assets of the company that must be maintained by fulfilling its needs and desires. However, the recent phenomenon indicates that the organizational performance of the company is still low, and there are numerous employees that are lack of competitiveness and productivity in carrying out their duties. Due to this reason, the researchers are interested in analyzing the correlation between commitment and organizational performance. The researchers utilized a causal research design to empirically test the correlation between commitment and organizational performance. One of the factors that is perceived to affect the employee performance is the organizational capabilities. The primary data of the study were collected by administering the questionnaire to the employees who work in manufacturing and service companies. The questionnaire was spread through e-mail to 100 respondents, and of the 100 respondents, 34 returned the answers. The data were then analyzed by using SPSS 25 through which the t-value test of the simple linear regression was determined. The results indicated that the commitment has a positive and significant correlation with the organizational performance. Every time there is a strengthening of commitment, there will be an increase in the organizational performance. This study shares similar findings with the previous studies. The implications of this research can be applied managerially by manufacturing and service companies. This finding is what distinguishes the present study from the previous research in which the latter is only applied for the service sector.